Key factors influencing target capital structure of property firms in Malaysia - Haron, Razali (Canadian Center of Science and Education, 2014)
Very limited studies have been done on the capital structure of property firms in Malaysia emphasizing on the presence of target capital structure and the affecting determinants and also the speed of adjustment to target leverage. Thus, this study aims to investigate these issues among the property firms in Malaysia by using a dynamic model. This study finds that these property firms do practice target capital structure which is influenced by certain firm characteristics like non-debt tax shield, asset structure, profitability, firm size, growth opportunity and liquidity in their capital structure and they also time their security issuance. Being deviated from target from time to time these property firms partially adjust indicating a support for the dynamic trade-off theory. There are also influences of the pecking order and the market timing theories in the capital structure decisions of these property firms. This study contributes to the literature by offering insights of the capital structure practice and the adjustment speed to target capital structure of property firms in Malaysia and fills the gap in the literature.